Parents' evaluations of genetic counselling. - Black, Rita Beck (Patient Counselling and Health Education, 1980)
Genetic counselling represents a new and important health service, but little is known about how the clients of genetic clinics actually experience and view the genetic counselling process. This paper reports on the evaluations made by clients of a genetics clinic and their recommendations for ways to improve and expand this service. In their comments, clients stressed the need for more time and individual attention from genetic counsellors, additional follow-up and supportive counselling, and increased efforts to educate the general public about birth defects. Their recommendations are discussed in terms of the implications for developing and improving genetic counselling services.
Keywords: anxiety; dept.swk; genetic counseling; heredity; medical education; medical examination; parent; prevention